Road to perdition [videorecording (DVD)] - Mendes, Sam; Hanks, Tom; Newman, Paul, 1925-2008; Law, Jude, 1972-; Leigh, Jennifer Jason, 1962-; Tucci, Stanley; Craig, Daniel, 1968-; Hoechlin, Tyler, 1987-; Collins, Max Allan (DreamWorks Home Entertainment, 2002)
Michael Sullivan works as an enforcer for his adopted father, Irish gangster John Rooney. When Sullivan's son, Mike Jr., witnesses one of his father's killings on Rooney's behalf, the gangster decides that his ward and his family are liabilities that must be removed. Sullivan tries to safeguard his son and get even with the man who betrayed him, while his son focuses on bonding with his emotionally distant father.